2019
DOI: 10.1002/14651858.cd013422
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of distal deep vein thrombosis

Abstract: BackgroundThe treatment of distal (below the knee) deep vein thrombosis (DVT) is not clearly established. Distal DVT can either be treated with anticoagulation, or monitored with close follow-up to detect progression to the proximal veins (above the knee), which requires anticoagulation. Proponents of this monitoring strategy base their decision to withhold anticoagulation on the fact that progression is rare and most people can be spared from potential bleeding and other adverse e ects of anticoagulation. Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…13 In addition, while the choice of treating distal DVT is still debated, particularly in low-risk patients, in patients with active cancer continuing to give therapeutic anticoagulation seems advisable. 14,15 The present study, which is the first prospective study specifically designed to validate the Ottawa score, has several strengths. The short period of inclusion (11 months) makes it unlikely that major changes in anticancer treatments could have influenced the study results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13 In addition, while the choice of treating distal DVT is still debated, particularly in low-risk patients, in patients with active cancer continuing to give therapeutic anticoagulation seems advisable. 14,15 The present study, which is the first prospective study specifically designed to validate the Ottawa score, has several strengths. The short period of inclusion (11 months) makes it unlikely that major changes in anticancer treatments could have influenced the study results.…”
Section: Discussionmentioning
confidence: 98%
“…Splanchnic vein thromboses also represent a different entity and should be analyzed separately (13). In addition, while the choice of treating distal DVT is still debated, particularly in low-risk patients, in patients with active cancer continuing to give therapeutic anticoagulation seems advisable (14,15). The present study, which is the first prospective study specifically designed to validate the Ottawa score, has several strengths.…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…The Cochrane Library recently collated a systematic review pertaining to management of distal DVT. Kirkilesis et al, evaluated 8 RCT involving both nonsurgical and surgical patients which included 1,239 participants with distal DVT who were randomized to treatment with anticoagulation with vitamin K antagonists or no anticoagulation 752 . There was no difference with respect to development of PE (relative risk [RR] 0.81, 95% confidence interval [CI] 0.18 – 3.59) between the treatment groups.…”
Section: - How Should Patients With Post-operative Distal Dvt Be Mana...mentioning
confidence: 99%
“…3 This systematic review and meta-analysis includes five randomized controlled trials (n = 503 patients) comparing anticoagulation with no intervention or placebo for the treatment of distal DVTs as well as three randomized controlled trials (n = 736 patients) comparing anticoagulation for 6 weeks versus 12 weeks or more. 4 The trials included adults over 18 years of age with a distal DVT identified on ultrasound or venography. The primary outcomes were recurrence of VTE (defined as DVT recurrence in the calf veins, progression of DVT to proximal veins, and pulmonary embolism [PE]) and major bleeding (defined as a 2 g/dL decrease in hemoglobin, transfusion of ≥2 units of red blood cells, bleeding in a critical site, or bleeding contributing to death).…”
Section: Narrativementioning
confidence: 99%
“…This systematic review and meta‐analysis includes five randomized controlled trials ( n = 503 patients) comparing anticoagulation with no intervention or placebo for the treatment of distal DVTs as well as three randomized controlled trials ( n = 736 patients) comparing anticoagulation for 6 weeks versus 12 weeks or more 4 . The trials included adults over 18 years of age with a distal DVT identified on ultrasound or venography.…”
Section: Narrativementioning
confidence: 99%